Parmenides's prooimion - Kubok, Dariusz (Folia Philosophica, 2000)
The article aim at an analysis of the prologue (prooimion) of Parmenides’s poem. The statements that it includes, which are given a mythical and allegorical form, allow us to have a comprehensive view on the nature of the intellectual breakthrough that took place owing to that great Greek thinker. The terms used in the prologue (such as themis, noos. dike, ananke. moyra), while being characteristic of a mythical imagery, contain profound philosophical insights which permanently changed the status of the philosophical inquiry by the first lovers of wisdom. The distinction between truth and judgement, together with the philosophical characteristics of these notions, crowns the whole prologue, and represents a decisive quantum leap in thinking giving rise to strictly ontological inquiries.